Tissue Imprint for Molecular Mapping of Deep Surgical Margins in Patients with Head and Neck Squamous Cell Carcinoma - Roh, Jong-Lyel (2012)
BACKGROUND: Tissue imprinting can generate molecular marker maps of tumor cells at deep surgical margins. This study evaluates the feasibility of this method for detection of residual head and neck squamous cell carcinoma (HNSCC). METHODS: Paired fresh tissue and nitrocellulose membrane imprints of tumor and deep margins were collected from 17 HNSCC resections. DNA was amplified using quantitative methylation-specific PCR (qMSP) for p16, DCC, KIF1A, and EDNRB. Levels of methylation in tumors and deep margins were compared. RESULTS: DNA from imprints was adequate for qMSP. Hypermethylation of target genes was present in 12/17 tumors and in 8 deep margins. Methylation level was better from margin imprints than tissue. During follow-up (median 13 months), local or regional recurrences occurred in six cases of which five had molecularly positive margins. CONCLUSION: Tissue imprinting is feasible for molecular detection of residual tumor at deep surgical margins and may correlate with locoregional recurrence.